EVALUATION OF GEOMETRY TEXTBOOKS THROUGH THE COGNITIVE POINT OF VIEW - İnam, Bahattin; Turanlı, Necla (International Online Journal of Education and Teaching, 2024)
The importance of cognitive approach in geometry education is increasing. In this direction, curriculum programs are renewed. One of the guides that teachers consider when applying the renewed curriculum in their classrooms is textbooks. Textbooks are used in many areas such as the order of the subjects, their boundaries and assessment and evaluation questions. From this point of view, the aim of the study is to evaluate geometry textbooks from a cognitive perspective. The research was carried out as a qualitative descriptive research. The sample of the research consists of two different 9th grade mathematics textbooks accepted after the last update. The assessment and evaluation questions in the textbooks and the tools, equipment, DGS and daily life examples used in the contents were evaluated separately by document analysis. Assessment and evaluation questions TIMSS-2019 assessment framework was used. As a result, it was determined that almost all of the questions used were in the application cognitive domain. It was observed that the obtained values were different from the ratios determined by TIMSS. It was concluded that a limited number of tools and equipment were used in the contents.